2021
DOI: 10.1097/md.0000000000026631
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular disease and prevention among people living with HIV in South Florida

Abstract: Antiretroviral therapy (ART) has improved survival of patients living with HIV (PLWH); however, this has been accompanied by an increase in cardiovascular disease (CVD). Although preventative measures for CVD among the general population are well described, information is limited about CVD prevention among PLWH. The goal of this study was to characterize the prevalence of CVD in our population and to assess the use of primary and secondary prevention. We performed a retrospective review of PLWH rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 62 publications
0
7
0
1
Order By: Relevance
“…Ge y col (Ge & Brown, 2020) añaden la determinación del perfil lipídico, prueba de esfuerzo cardiaco, tomografía computarizada cardiaca, el uso de estas pruebas pueden ayudar a reducir la mortalidad por enfermedades cardiovasculares a través de una detección más temprana de la enfermedad o una evaluación de riesgo más precisa. Pyarali y col (Pyarali et al, 2021) destacan la utilidad de la medición de células T CD4 y determinación del perfil lipídico, se demostró que el recuento de CD4 tiene un efecto protector mínimo contra la ECV. Particularmente Woldoyes y col. (Woldeyes et al, 2022b) mencionaron que la ecocardiografía es un método diagnostico no invasivo mucho más detallado y de gran valor, el cual evidencia la prevalencia de múltiples anomalías cardiacas en pacientes con VIH.…”
Section: Discussionunclassified
“…Ge y col (Ge & Brown, 2020) añaden la determinación del perfil lipídico, prueba de esfuerzo cardiaco, tomografía computarizada cardiaca, el uso de estas pruebas pueden ayudar a reducir la mortalidad por enfermedades cardiovasculares a través de una detección más temprana de la enfermedad o una evaluación de riesgo más precisa. Pyarali y col (Pyarali et al, 2021) destacan la utilidad de la medición de células T CD4 y determinación del perfil lipídico, se demostró que el recuento de CD4 tiene un efecto protector mínimo contra la ECV. Particularmente Woldoyes y col. (Woldeyes et al, 2022b) mencionaron que la ecocardiografía es un método diagnostico no invasivo mucho más detallado y de gran valor, el cual evidencia la prevalencia de múltiples anomalías cardiacas en pacientes con VIH.…”
Section: Discussionunclassified
“…It is estimated that several factors contribute to cardiovascular mortality in PLWH. One of them is the increased life expectancy in PLWH and the age-related cardiovascular changes; others include HIV infection, poor infection control, chronic inflammation, immunologic progression (low CD4+ cell count), and ART-mediated cardiometabolic dysfunction [7,15,19].…”
Section: Discussionmentioning
confidence: 99%
“…The therapy consists of two nucleoside reverse transcriptase inhibitors (NRTI) and one protease inhibitor (PI) or one non-nucleoside reverse transcriptase inhibitor (NNRTI) or one integrase inhibitor and a C-C chemokine receptor 5 (CCR5) inhibitor [21]. Previous research concluded that, besides their substantial benefits, ART is associated with metabolic changes and increased CVD risk, including atherosclerosis [3,6,7,16]. Few antiretroviral drugs are known to induce OS by several biochemical reactions.…”
Section: Anti-retroviral Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the introduction of potent antiretroviral therapy (ART), despite achieving undetectable virus levels in blood, many patients with chronic treated human immunodeficiency virus (HIV) have evidence of continued inflammation and increased risk of cardiovascular disease [ 46 ]. The continued inflammation is thought to be attributed to the persistence of intracellular virus (e.g.…”
Section: Gut-derived Lipopolysaccharide Oxidized Lipids and Apoa-i Mi...mentioning
confidence: 99%